From Diagnoses to Ongoing Journey: Parent Experiences Following Congenital Heart Disease Diagnoses. (10th July 2019) - Williams, Tricia S; McDonald, Kyla P; Roberts, Samantha D; Chau, Vann; Seed, Mike; Miller, Steven P; Sananes, Renee
Abstract: Despite improved survival among children with congenital heart disease (CHD), the risk of psychosocial difficulties remains largely unchanged with an increased emphasis of improving support for parents as a mechanism to optimize outcomes. Objective: Using qualitative and quantitative methods, the current cross-sectional study examined parents' experiences at the time of their child's diagnosis, what they thought helped their child recover, barriers to support, and identified needs for future models of care. Method: The sample included 26 parents (22 mothers, 3 fathers, and 1 mother/father pair) of children with CHD, ranging in age between 6 months and 4 years with a mean age of 2 years. Results: Qualitative results were organized around five themes: (a) They (medical team) saved my child's life, (b) My child is going to be okay, (c) Not out of the woods, (d) Optimizing support for my child and myself, and (e) What still gets in the way. Parents uniformly expressed a need for greater mental health support for their children as well as programs to improve parents' skill and confidence, with no difference between age groups (< 2 years and > 2 years of age). Common barriers to service included distance and time off work. Conclusion: Parents' experiences informed both acute and long term implications following CHD diagnoses, and highlight current gaps in mental health care. Direction for clinical care and improved intervention opportunities are discussed.